A paracrine activin A–mDia2 axis promotes squamous carcinogenesis via fibroblast reprogramming - Cangkrama, Michael; Wietecha, Mateusz; Mathis, Nicolas; Okumura, Rin; Ferrarese, Luca; Al‐Nuaimi, Dunja; Antsiferova, Maria; Dummer, Reinhard; Innocenti, Metello; Werner, Sabine (EMBO molecular medicine, 2020)
Cancer‐associated fibroblasts (CAFs) are key regulators of tumorigenesis and promising targets for next‐generation therapies. We discovered that cancer cell‐derived activin A reprograms fibroblasts into pro‐tumorigenic CAFs. Mechanistically, this occurs via Smad2‐mediated transcriptional regulation of the formin mDia2, which directly promotes filopodia formation and cell migration. mDia2 also induces expression of CAF marker genes through prevention of p53 nuclear accumulation, resulting in the production of a pro‐tumorigenic matrisome and secretome. The translational relevance of this finding is reflected by activin A overexpression in tumor cells and of mDia2 in the stroma of skin cancer and other malignancies and the correlation of high activin A/mDia2 levels with poor patient survival. Blockade of this signaling axis using inhibitors of activin, activin receptors, or mDia2 suppressed cancer cell malignancy and squamous carcinogenesis in 3D organotypic cultures, ex vivo, and in vivo , providing a rationale for pharmacological inhibition of activin A‐mDia2 signaling in stratified cancer patients. Synopsis The growth and differentiation factor A induces differentiation of fibroblasts into tumor‐promoting cancer‐associated fibroblasts, thereby promoting cutaneous squamous carcinogenesis. Activin A promoted malignancy of squamous cell carcinoma in a non‐cell autonomous manner. Activin A induced a pro‐migratory and tumor‐promoting phenotype in fibroblasts via its direct target mDia2. mDia2 suppressed p53 activity in fibroblasts via direct protein‐protein interaction. Inhibition of the activin A‐mDia2 axis suppressed skin tumor growth. Graphical Abstract The growth and differentiation factor A induces differentiation of fibroblasts into tumor‐promoting cancer‐associated fibroblasts, thereby promoting cutaneous squamous carcinogenesis.